Association between evidence-based training and clinician proficiency in electronic health record use. (12th February 2021) - Hollister-Meadows, Laura; Richesson, Rachel L; Gagne, Jennie De; Rawlins, Neil
Abstract: Objectives: The purpose of the study was to determine if association exists between evidence-based provider training and clinician proficiency in electronic health record (EHR) use and if so, which EHR use metrics and vendor-defined indices exhibited association. Materials and Methods: We studied ambulatory clinicians' EHR use data published in the Epic Systems Signal report to assess proficiency between training participants (n = 133) and nonparticipants (n = 14). Data were collected in May 2019 and November 2019 on nonsurgeon clinicians from 6 primary care, 7 urgent care, and 27 specialty care clinics. EHR use training occurred from August 5 to August 15, 2019, prior to EHR upgrade and organizational instance alignment. Analytics performed were descriptive statistics, paired t-tests, multivariate correlations, and hierarchal multiple regression. Results: For number of appointments per 30-day reporting period, trained clinicians sustained an average increase of 16 appointments ( P < .05), whereas nontrained clinicians incurred a decrease of 8 appointments. Only the trained clinician group achieved postevent improvement in the vendor-defined Proficiency score with an effect size characterized as moderate to large (dCohen = 0.625) Discussion: Controversies exist on the return of investment from formal EHR training for clinician users. Previously published literature has mostly focused on qualitative data indicators of EHR training success. The findings of our EHR use training study identified EHR use metrics and vendor-defined indices with the capacity for translation into productivity and generated revenue measurements. Conclusions: One EHR use metric and 1 vendor-defined index indicated improved proficiency among trained clinicians.